Structure of a heavily transcribed region of barley chloroplast DNA. Transfer RNA genes for serine (UGA), glycine (GCC, UCC), formyl-methionine and threonine (GGU) - Oliver, Richard; Poulsen, C. (1984)
The barley chloroplast genome is transcribed into at least 80 RNA molecules (29). Some regions of the genome hybridise to more transcripts than others. One 4.3 kbp HindIII fragment was found to hybridise to a disproportionately high number of transcripts, some of which were light-induced. The sizes of the transcripts ranged from 0.3 to 5.5 kb. In order to discover from which genes these transcripts are derived, the DNA sequence of the fragment has been determined and the transcripts have been mapped. Five tRNA genes have been located including genes for formyl-methionine tRNA and a glycine tRNA with an intron in the D-stem. A scheme to account for the transcription and processing of a precursor-transcript for these tRNAs is proposed. A region containing two open-reading frames hybridises to 9 transcripts. The largest of these, which is 5.5 kb, may be intercistronically processed. A number of long repeated sequences which may be involved in recombinational activity were found.